2020
DOI: 10.48550/arxiv.2010.00340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The groups of diffeomorphisms and homeomorphisms of 4-manifolds with boundary

Abstract: We give constraints on smooth families of 4-manifolds with boundary using Manolescu's Seiberg-Witten Floer stable homotopy type, provided that the fiberwise restrictions of the families to the boundaries are trivial families of 3-manifolds. As an application, we show that, for a simply-connected oriented compact smooth 4-manifold X with boundary with an assumption on the Frøyshov invariant or the Manolescu invariants α, β, γ of ∂X, the inclusion map Diff(X, ∂) ֒→ Homeo(X, ∂) between the groups of diffeomorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…To our knowledge, there is no known counter example to this conjecture. Positive evidence to the non-surjectivity of the maps is given in [36] where nonsurjectivity is shown that for certain W , which is a partial generalization of results for closed 4-manifolds in [9,15,21,22,35,46] to 4-manifolds with boundary.…”
Section: Introductionmentioning
confidence: 78%
“…To our knowledge, there is no known counter example to this conjecture. Positive evidence to the non-surjectivity of the maps is given in [36] where nonsurjectivity is shown that for certain W , which is a partial generalization of results for closed 4-manifolds in [9,15,21,22,35,46] to 4-manifolds with boundary.…”
Section: Introductionmentioning
confidence: 78%
“…Furthermore, we expect that it should be possible to consider more detailed applications to the question of when a family of three-manifolds extends to a family of 4-manifolds with boundary. Compare with recent work of Konno-Taniguchi [KT20] in the case that the boundary family of 3-manifolds is the trivial family of a rational homology sphere.…”
mentioning
confidence: 74%
“…Recall the comuputation of Manolescu's α invariant of Y (see [55, Proposition 3.8, Page 172]):α(Σ(2, 3, 12k + 1)) = 0, α(−Σ(2, 3, 12k + 1)) = −γ(α(Σ(2, 3, 12k + 1))) = 0, α(−Σ(2, 3, 12k − 1)) = −γ(α(Σ(2, 3, 12k − 1))) = 0.Thus in any case we have α(Y ) = 0. Then it follows from[44, Theorem 1.2] that −σ(W )/8 ≤ α(Y ) = 0, but since σ(W ) = −16, this is a contradiction.Bryan proved in [12, Theorem 1.8] that, for a spin odd involution ι on a spin rational cohomology K3 surface X, we have b + ι (X) = 1. If f in Proposition 5.4 is an involution ι, then Proposition 5.4 implies that b + ι (W ) = 1 or b + ι (W ) = 3.…”
mentioning
confidence: 97%